Efecto aplicación de inoculantes sobre la efecto de la aplicación de inoculantes sobre las características microbianas a los 60 días de ensilaje de maíz forrajero (Zea mayz L). Mocache, Ecuador 2013 - Narváez Aranda, Diego Stalin (2013)
The objective was to determine the effect of application of microbial inoculants on silage forage maize (Zea mays L). The crop is harvested as 60 days. PVC microsilos where fodder maize 3 kg were used approximately deposited including Lacto more Silo and Sil -All, where a solution containing 750 ml of distilled water with the addition of 1.8 grams of each inoculant is prepared each microsilo added 62.5 Ml of inoculum solution. At microsilos they were also added molasses as a source of soluble carbohydrates. T1 corn silage + molasses without inoculum ; ; T2 corn silage + molasses + Sil -All ® 4 x 4 , 3 treatments with six replications was used , with a total of 18 microsilos distributed in a completely randomized design T3 corn silage + + Lacto Silo ® molasses and fermentation period ( 60 days) was evaluated . The variables evaluated were: microbial composition (bacteria, lactobacilli, yeasts and molds). The results demonstrate that in the process of silage by the addition of bacterial inoculants significant differences ( p > 0.05 ) was found in the growth of bacteria, T3 ( Lacto Silo) reached the highest growth (9.43 CFU mL-1 ) , this indicates if it caused effect for this variable, while for lactobacilli , fungi and yeasts found no significant differences . It is concluded that the process of silage corn silage with the inclusion of these inoculants introduced change, therefore, was a good choice to improve silage quality of the final product